Clinical and fiberoptic endoscopic assessment of swallowing in patients with chronic obstructive pulmonary disease - Macri,Marina Rodrigues Bueno (2013)
INTRODUCTION: Chronic obstructive pulmonary disease is characterized by progressive and partially reversible obstruction of pulmonary airflow. AIM: To characterize swallowing in patients with chronic obstructive pulmonary disease and correlate the findings with the degree chronic obstructive pulmonary disease, heart and respiratory rate, oxygen saturation, and smoking. METHOD: We conducted a prospective cohort study of 19 patients (12 men and 7 women; age range, 50-85 years) with confirmed medical diagnosis of chronic obstructive pulmonary disease. This study was performed in 2 stages (clinical evaluation and functional assessment using nasolaryngofibroscopy) on the same day. During both stages, vital signs were checked by medical personnel. RESULTS: Clinical evaluation of swallowing in all patients showed the clinical signs of cough. The findings of nasolaryngofibroscopy highlighted subsequent intraoral escape in 5 patients (26.5%). No patient had tracheal aspiration. There was no association of subsequent intraoral escape with degree of chronic obstructive pulmonary disease, heart and respiratory rate, oxygen saturation, or smoking. CONCLUSION: In patients with chronic obstructive pulmonary disease, there was a prevalence of oral dysphagia upon swallowing and nasolaryngofibroscopy highlighted the finding of subsequent intraoral escape. There was no correlation between intraoral escape and the degree of chronic obstructive pulmonary disease, heart and respiratory rate, oxygen saturation, or smoking.